Critical behavior of polycrystalline Pr0.7Ca0.1Sr0.2MnO3 exhibiting the crossover of first and second order magnetic phase transitions - Nguyen Thi Dung (Journal of Materials Research and Technology, 2020)
A polycrystalline ceramic of Pr0.7Ca0.1Sr0.2MnO3 was prosperously synthesized by the solid-state reaction method. The M(T, H) data measured at different temperatures in applied magnetic fields H = 0–30 kOe showed that the material has a ferromagnetic-paramagnetic phase transition and exhibits the crossover of the first and second order magnetic phase transitions. Above Curie temperature (TC), the χ−1(T) curve witnesses a downturn in the paramagnetic region, suggesting an appearance of the Griffiths phase. Using the modified Arrott plots and the Kouvel-Fisher methods, we have identified a set of the critical parameters (TC, β, γ, and δ) for Pr0.7Ca0.1Sr0.2MnO3 compound. The results are found to be TC = 205.5 ± 0.1 K, β = 0.191 ± 0.010, γ = 0.856 ± 0.016 and δ = 5.649 ± 0.030. It can be seen that the values of the exponents β, γ, and δ are quite close to the exponents of the tricritical mean field model. Additionally, they ​​satisfy the scaling theory well, proving their reliability. Based on obtained results, we suggest that the ferromagnetic-paramagnetic transition in Pr0.7Ca0.1Sr0.2MnO3 compound is located at a crossover of the first and second order transformations.